2016
DOI: 10.1111/tct.12495
|View full text |Cite
|
Sign up to set email alerts
|

An advocacy experience for medical students

Abstract: A brief clinical experience outside of a traditional health care setting in which students are exposed to the day-to-day reality of advocating for vulnerable populations can meaningfully contribute to a comprehensive advocacy curriculum. We suggest this programme could be feasibility adapted to other settings and populations. The importance of supportive and reflective mentorship and diverse clinical settings are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Homeless myths and misconceptions busted. [4][5][6][7][8][9][10][11] Myth The veterans in our homeless shelter population over the preceding six years vary from 20% to 34% at any given time. Many have full service related benefits and many qualify for permanent housing.…”
Section: Learner Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Homeless myths and misconceptions busted. [4][5][6][7][8][9][10][11] Myth The veterans in our homeless shelter population over the preceding six years vary from 20% to 34% at any given time. Many have full service related benefits and many qualify for permanent housing.…”
Section: Learner Outcomesmentioning
confidence: 99%
“…12 From examining multiple established references addressing service learning in many disciplines, the emotional architecture of learned experience is an under-recognized element in the creation of professional identity and needs to be formally studied and documented for its ability to ''fastforward'' long-term commitment to care and caring as well as promoting physician satisfaction and being a potential ''vaccine'' against burnout. [13][14][15][16][17][18][19][20][21][22] Summary DOTS, a critical service learning experience, improves the human connection between learners in health-care professions and individual shelter participants. Through a diminished focus on creating an expert role and administrative tasks, participants report that obtaining the narrative story improved sensitivity to and empathy for patients' experiences.…”
Section: Learner Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Curricula might include instruction on advocacy and provide hands-on opportunities to press for local and regional changes in policy and health care delivery. Baribeau and colleagues [25] integrated homeless health into a family medicine clerkship. They demonstrated that a mandatory clinical experience in homeless health can meaningfully contribute to a comprehensive advocacy curriculum.…”
Section: -John Howard Paynementioning
confidence: 99%
“…In this issue of the journal, Baribeau et al. write of an initiative involving medical students receiving advocacy training during placements with the homeless and vulnerably housed . These placements may be challenging for learners, one of whom reports ‘feeling overwhelmed’.…”
mentioning
confidence: 99%